(untitled) (International Journal of Economics Management and Social Science, 2026)
Modern container and tanker operations depend heavily on tacit knowledge—experiential understanding that experienced seafarers possess but struggle to articulate systematically—yet maritime education primarily emphasizes formal procedural knowledge. This qualitative ethnographic study examined mentorship processes aboard 16 commercial vessels (8 container ships, 8 tankers) over 18 months, combining 156 hours of bridge observation, 72 semi-structured interviews with experienced captains, chief officers, and junior officers, and analysis of 47 critical incident reports. Findings reveal that despite high-quality maritime academy training, junior officers consistently require 18-24 months post-certification to achieve practical competency in real-world bridge operations, with knowledge gaps concentrated in: judgment development for weather decision-making, interpretation of crew behavior and condition monitoring, understanding vessel-specific behavioral characteristics, and communication across hierarchical and language-diverse bridge teams. Traditional mentorship occurs informally through observation and correction, often hindered by language barriers (particularly on multinational crews), hierarchical communication constraints limiting junior officers’ questions, and time pressures limiting deliberate teaching. A pilot intervention integrating video documentation of exemplary decisions, structured reflection prompts, and peer discussion platforms demonstrated feasibility (adoption rate 68%, user satisfaction 4.1/5.0) and produced measurable improvements in junior officer decision-making speed and confidence. Findings establish that intentional knowledge transfer structures—combining formal mentorship training for senior officers, digital tools supporting asynchronous documentation and peer learning, and organizational cultures permitting psychological safety for questions—can substantially reduce the tacit knowledge acquisition period while enhancing crew safety and operational efficiency. Keywords : Tacit knowledge; Mentorship; Maritime operations; Knowledge transfer; Deck bridge operations; Seafarer training; Multinational crews